2015
DOI: 10.1007/s11356-015-4488-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of diesel oil by a novel microbial consortium: comparison between co-inoculation with biosurfactant-producing strain and exogenously added biosurfactants

Abstract: Bioremediation, involving the use of microorganisms to detoxify or remove pollutants, is the most interesting strategy for hydrocarbon remediation. In this aim, four hydrocarbon-degrading bacteria were isolated from oil-contaminated soil in Tunisia. They were identified by the 16S rDNA sequence analysis, as Lysinibacillus bronitolerans RI18 (KF964487), Bacillus thuringiensis RI16 (KM111604), Bacillus weihenstephanensis RI12 (KM094930), and Acinetobacter radioresistens RI7 (KJ829530). Moreover, a lipopeptide bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 56 publications
0
31
0
2
Order By: Relevance
“…show that the addition of surfactant makes hydrocarbons more available to degradation and cocultures with B. subtilis (red) and A. radioresistans (purple) producing biosurfactants enable better contaminant degradation than the degrader strains alone. [72] b. Bioenergy from complex feedstocks. The fungi Trichoderma reseei (green) secretes cellulase which degrades weed lignocellulose into accessible saccharides (black hexagons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…show that the addition of surfactant makes hydrocarbons more available to degradation and cocultures with B. subtilis (red) and A. radioresistans (purple) producing biosurfactants enable better contaminant degradation than the degrader strains alone. [72] b. Bioenergy from complex feedstocks. The fungi Trichoderma reseei (green) secretes cellulase which degrades weed lignocellulose into accessible saccharides (black hexagons).…”
Section: Discussionmentioning
confidence: 99%
“…Diesel biodegradation was more successful in cocultures with surfactant producers than in cultures of degraders alone (Figure 4a). [72] Movement towards a greener economy will be aided by consortia, notably in the areas of renewable feedstocks, bioproduction, and biofuels. For example, consider the growth of oleaginous microalgae for the production of biofuels.…”
Section: Building Communicationmentioning
confidence: 99%
“…Our recent study confirmed that bioaugmentation of B. subtilis SE1 together with nutrient biostimulation enhanced substantially biodegradation of gasoline contaminated in soil. In fact, supplementation of biosurfactant producing bacteria into polluted sites may provide more practical than addition of exogenous biosurfactant produced in fermentation reactors because of avoiding high cost arising from production and preparation of purified biosurfactants (Mnif et al, 2015). However, in situ biodegradation success of hydrocarbons depends on the selection of biosurfactant producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bioaugmentation of biosurfactant-producing Nimrat et al 495 microorganisms in hydrocarbon polluted soils is an interesting method that would generate a continuous supply of a non-toxic and biodegradable surfactant and promote the rate of biodegradation (Mnif et al, 2015). Therefore, this study was designed to evaluate B. subtilis SE1 ability to enhance biodegradation of gasoline, diesel oil, crude oil and used engine oil in soils under laboratoryscale bioremediation condition.…”
Section: Introductionmentioning
confidence: 99%
“…From an applied perspective, utilization of a microbial consortium is more advantageous than the use of a pure culture, due to its greater metabolic diversity and increased ability to adapt to the field conditions [117]- [119]. Thus, the use of microbial consortia is a good alternative to clean up the oil-contaminated sites, and even when the sites are co-infected by another pollutant.…”
Section: Bioaugmentationmentioning
confidence: 99%